Food label and package survey status of children's drink in the Philippines - Manila, Anthony P. (2004)
ABSTRACT The study primarily involved a survey of labels of a variety of fruit drinks Filipino children usually consume. Mandatory labeling requirements and other parts of a food label usually seen were checked for its presence on every food item. All fruit drinks contained food additives that are safe for consumption, with the exception of powdered fruit drinks, which contained some allergens. A large percentage of samples, most notably the powdered fruit juices, have preservatives or additives incorporated in them. The fortification with vitamin A utilized different forms of vitamin A in several fruit drinks, like beta-carotene, vitamin A palmitate, and vitamin A acetate. Nearly all samples contain citric acid. Vitamin C was the most predominant food fortificant used among fortifies samples. It was also the only nutrient that provided 100% RDA (Recommended Dietary Allowance) based on a 2,000 calorie diet. In terms of ingredients, natural color/flavor/juice was more predominant than the nature-identical and artificial color/flavor. Although not a mandatory labeling requirement in the Philippines, ninety eight percent of the samples contained nutritional labels. Nutrition information may be included on the label or in the labeling provided it conforms to the requirements set by the Bureau of Food and Drugs.